2019
DOI: 10.24154/jhs.2019.v14i02.015
|View full text |Cite
|
Sign up to set email alerts
|

Pod set and Pollen Viability Studies in Yard Long Bean (Vigna unguiculata sub sp. sesquipedalis)

Abstract: A study was conducted in a yard long bean (Vigna unguiculata sup/ssp. sesquipedalis) hybrid VS 50 (Kakkamoola Local) x VS 26 (Vellayani Jyothika) to assess the percentage fruit set at two time intervals and to identify the best time interval for pollination in yard long bean hybrids. Hand pollination was done using VS 50 as female parent and VS 26 as male parent for seven consecutive days at two time intervals, 6.30 – 7.30 am and 7.30 – 8.30 am. Higher percentage of fruit set (36.8 %) was observed between 6:30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The rate of successful in hand pollination revealed by this study is comparable to hand pollination success of 2.3 -22.5 % in beans reported by Bhanu et al (2018). Similarly, Merin et al (2019) reported rate of successful in bean hand pollination of 23.8 %, while Vollmann et al (1992) reported rate of successful in hand pollination of beans below 18 %. The low pod setting of the hand pollinated flowers in beans is reported to be due to failure of the pollen tubes to penetrate the stigma and in some cases, fertilization occurs, but embryo abortion takes place due high temperature above 23 ˚C, genetic response of the parents and relative humidity below 45 or higher than 55 (Bhanu et al, 2018).…”
Section: Common Bean F2 Lines Seed Iron and Zinc Contentssupporting
confidence: 82%
“…The rate of successful in hand pollination revealed by this study is comparable to hand pollination success of 2.3 -22.5 % in beans reported by Bhanu et al (2018). Similarly, Merin et al (2019) reported rate of successful in bean hand pollination of 23.8 %, while Vollmann et al (1992) reported rate of successful in hand pollination of beans below 18 %. The low pod setting of the hand pollinated flowers in beans is reported to be due to failure of the pollen tubes to penetrate the stigma and in some cases, fertilization occurs, but embryo abortion takes place due high temperature above 23 ˚C, genetic response of the parents and relative humidity below 45 or higher than 55 (Bhanu et al, 2018).…”
Section: Common Bean F2 Lines Seed Iron and Zinc Contentssupporting
confidence: 82%
“…The overall rate is 49.82% lower compared to Yard Long Bean (Vigna unguiculata subsp. sesquipedalis) (46).…”
Section: Pollen Viability Assaymentioning
confidence: 99%